FORMULASI SEDIAAN MOUTHWASH DARI SARI BUAH SIRIH (Piper betle L.) VARIETAS SIRIBOAH - Ririn, Ririn; Tandjung, Amran Ilyas; Wagola, Sarif (Jurnal Ilmiah As-Syifaa, 2013)
Piper betle fruit empirically is believed to maintain  oral health, but unfortunately the use of piper betle fruit not to be proven scientifically, therefore one of the efforts in explore benefits of betel fruit is to formulatedinto mouthwash. The aim of this research was to prepared stable and effective mouthwash preparation which is inhibit the growth of Streptococcus mutans. There were 3 formula designed  by varying the concentration of the piper betle fruit juice 3, 4 and 5 % v/v respectively. Stability evalution carried out before and after accelerated condition at 5oC and  35oC for 10 cycles in which the parameter  were organoleptic, pH value, viscosity and inhibitory  Streptococcus mutans of the bacteria. The assay results of the inhibition of each formula with agar diffusion method showed that the 3 formula were able to inhibit the growth of Streptococcus mutans, but the most optimum stability and effective inhibiting Streptococcus mutans was formula F3,that contain 5% fruit juice,  due to there was no significant change before and after accelerated condition. Key word : Mouthwash, Piper betle fruit (Piper betle L.), Streptococcus mutans